Endothelial, pericyte and tumor cell expression in glioblastoma identifies fibroblast activation protein (FAP) as an excellent target for immunotherapy - Lisa M Ebert; Wenbo Yu; Tessa Gargett; John Toubia; Paris M Kollis; Melinda N Tea; Brenton W Ebert; Cedric Bardy; Mark van den Hurk; Claudine S Bonder; Jim Manavis; Kathleen S Ensbey; et al. (Clinical & Translational Immunology, 2020)
Abstract Objectives Targeted immunotherapies such as chimeric antigen receptor (CAR)‐T cells are emerging as attractive treatment options for glioblastoma, but rely on identification of a suitable tumor antigen. We validated a new target antigen for glioblastoma, fibroblast activation protein (FAP), by undertaking a detailed expression study of human samples. Methods Glioblastoma and normal tissues were assessed using immunostaining, supported by analyses of published transcriptomic datasets. Short‐term cultures of glioma neural stem (GNS) cells were compared to cultures of healthy astrocytes and neurons using flow cytometry. Glioblastoma tissues were dissociated and analysed by high‐parameter flow cytometry and single‐cell transcriptomics (scRNAseq). Results Compared to normal brain, FAP was overexpressed at the gene and protein level in a large percentage of glioblastoma tissues, with highest levels of expression associated with poorer prognosis. FAP was also overexpressed in several paediatric brain cancers. FAP was commonly expressed by cultured GNS cells but absent from normal neurons and astrocytes. Within glioblastoma tissues, the strongest expression of FAP was around blood vessels. In fact, almost every tumor vessel was highlighted by FAP expression, whereas normal tissue vessels and cultured endothelial cells (ECs) lacked expression. Single‐cell analyses of dissociated tumors facilitated a detailed characterisation of the main cellular components of the glioblastoma microenvironment and revealed that vessel‐localised FAP is because of expression on both ECs and pericytes. Conclusion Fibroblast activation protein is expressed by multiple cell types within glioblastoma, highlighting it as an ideal immunotherapy antigen to target destruction of both tumor cells and their supporting vascular network.